Military installations in the Ayyubid era: 567 AH-648 AH / 1172 AD-1250 AD - Merin, Forat; Al-Rawi, Qusay (Al-Adab Journal, 2024)
The Ayyubid state paid special attention to military installations to protect the state from the attacks of the Crusader enemies, including castles, which were built with stone and lime that were brought from the surrounding areas. And they took into account in choosing the site a healthy climate, so that health does not deteriorate with it and food does not spoil, and the delivery of water to the castle. In Egypt and the Levant, as well as "restoring some of the others and introducing additions to them, and providing them with weapons and military equipment, they also paid great attention to the walls, because the fortification of cities with walls reduces the risk of the city being penetrated by the enemy and provides them with sufficient time to take the necessary measures to confront the enemy, and this has been done Building walls of stones and using Frankish prisoners to build them. They also built military cities to fight the Franks, and due to the conditions of war in the Ayyubid state, it required the existence of an institution that surveys the conditions of the enemy, the Crusaders, knowing the types of their weapons, their equipment, and the extent of their strength. It also transfers information in complete secrecy to and from the outskirts of the country. Air and land mail lines. They also took care of the fleet and set aside for the navy a court known as (Divan of the Fleet) to spend on the navy. They established houses for the ship industry, which took over the manufacture of ships. The Court of the Fleet took charge of spending on these houses, and the Moroccans had a prominent role in the manufacture and leadership of the Ayyubid fleets.